Proactive Maintenance and Data-Driven Optimization of Mineral Lubricating Oil in a Gas Engine Cogeneration System Extending Oil Change Intervals for Cost Savings and a Reduced Environmental Footprint - Krzysztof Pytel; Roman Filipek; Adam Kalwar; Małgorzata Piaskowska-Silarska; Wiktor Hudy; Jana Depešová; Franciszek Kurdziel (Energies)
This study investigates the operational properties of mineral lubricating oil in gas engines used in cogeneration systems, with a focus on factors contributing to the degradation of lubricating properties critical for energy efficiency and system management. The research was conducted on a 4.3 MW gas engine operating for about 90,000 machine hours, using natural gas as fuel. Data obtained from SCADA (Supervisory Control and Data Acquisition) systems and laboratory analysis were utilized to establish oil quality criteria, enabling the prediction of oil degradation and optimization of oil change intervals. Parameters including viscosity, contamination levels, Total Base Number (TBN), and Total Acid Number (TAN), were identified as significant indicators of oil performance and engine reliability. The findings revealed that oil change intervals could be extended by an average of 37% compared to standard schedules, thereby minimizing unnecessary maintenance downtimes, enhancing system availability, and increasing electrical and thermal energy output. Optimized oil utilization reduced material costs for oil and filter replacements, lowering expenditures from 3021 to 1887 EUR per machine hour. Additionally, the predicted Global Warming Potential (GWP) for prematurely consumed oil amounted to 68 × 103 kg CO2 eq., while avoidable waste generation reached 18.2 m3 of mineral oil. Regular oil analysis conducted every 1000 operating hours proved critical for early detection of oil degradation, supporting proactive maintenance strategies and ensuring optimal engine performance and longevity.